Emerging research trends in medical textiles - Gokarneshan, N.; Rachel, D. Anitha; Rajenn, V.; Lavanya, B.; Ghoshal, Arundhathi (Springer Singapore, 2015)
This book provides a comprehensive review of the significant researches reported during the recent years in the field of medical textiles. It also highlights the use of new types of fibers in developing medical textile products and their promising role in the respective areas of application. Considerable developments have taken place in the development of medical textiles for varied applications.